Effect of hydrophobically modified PEO polymers (PEO-dodecyl) on oil/water microemulsion properties: in vitro and in silico investigations. Issue 12 (10th February 2021) - Khatouri, M.; Ahfir, R.; Lemaalam, M.; El Khaoui, S.; Derouiche, A.; Filali, M.
Abstract : In this work, we study the effect of grafted PEO-dodecyl co-polymers on the decane/water microemulsions properties. For this purpose, we combined the MD simulations, the OZ integral equations resolved using the HNC closure, and SANS experiments. Abstract : Microemulsions are excellent systems for transdermal delivery of multifunctional drugs because they have the potential to improve drug absorption/permeation and handling limitations. Biocompatible polymers are used as a coating of microemulsions to avoid the interactions that can occur between the microemulsions and the skin. Thus, they protect and lubricate these transporter nanovesicles. In this paper, we studied decane/water microemulsions covered with hydrophobically modified PEO polymer (PEO-m). To reveal the effect of hydrophobically modified PEO (PEO-m) polymer on the shape, the micro-arrangement and the dynamics of the microemulsions, we used an integrated strategy combining Molecular Dynamics simulation (MD), Small-Angle Neutron Scattering experiments (SANS), and the Ornstein–Zernike integral equations with the Hypernetted Chain (HNC) closure relation. We determined the microemulsion shape in vitro using the renormalized intensities spectra from SANS experiments. We discussed the micro arrangements of microemulsions, in vitro and in silico, employing the pair correlation function g ( r ) and the structure factor S ( q ), obtained from the three approaches with good agreement. Thus, we used the validated MD simulations to calculate the microemulsion's dynamics properties that we discussed using the mean-squared displacement (MSD) and the diffusion coefficients. We found that the presence of moderate quantities of PEO-m, from 4 to 12 PEO-m per microemulsion, does not influence the microemulsion shape, increases the stability of the microemulsion, and slightly decrease the dynamics. Our in vitro and in silico results suggest that polymer incorporation, which has interesting in vivo implications, has no disadvantageous effects on the microemulsion properties.